القرض السندي كوسيلة حديثة للتمويل - عميار, فتيحة (جامعة الوادي University of Eloued, 2017)
يعتبر القرض السندي وسيلة تمويل خارجية يتم عن طريق الاستدانة يتمثل في أوراق مالية تسمى بالسندات تتضمن قرضا يقوم بإصدارها المقترض سوى كانت حكومة او شركة او مؤسسة لمدة طويلة الاجل بغرض تمويل ما تتطلبه استثماراتها ومشاريعها الكبرى بحيث تعطي الحق للمقرض مقابلة قرضه الحصول على نسبة فائدة دورية واسترجاع دينه في تاريخ إستحقاقه . وهدا النوع من التمويل يعتبر اقل تكلفة مقارنة بالتمويل عن طريق الأسهم كدلك يتيح للشركة او المؤسسة فرصة المحافظة على استقلاليتها في التسيير عكس التمويل بالأسهم الذي يسمح بدخول شركاء جدد تكون لهم الاحقية في إدارة الشركة . والتمويل عن طريق السندات لا يسمح لاصحابها التدخل في إدارة الشركة وانما الحصول على الفوائد فقط وللسندات عدة أنواع نذكر منها : - حسب الجهة المصدرة وتنقسم الى أربعة أنواع : سندات دولية ,سندات دولة ,سندات الهيئات الحكومية ,السندات التي تصدرها المؤسسات المالية وشركات المساهمة - حسب نوع طريقة الضمان:سندات مرهونة باصول معينة , سندات عادية ليست لها ضمان . - حسب صفة المستفيد :سندات لحاملها ,سندات اسمية - حسب الاثار المترتبة عليها : سندات قابلة للتحويل , سندات غير قابلة للتحويل ,سندات ذات علاوة - حسب العملة التي تحرر بها :سندات تحرر بالعملة الوطنية للجهة المصدرة ,سندات تحرر بعملات اجنبية بالنسبة للجهة المصدرة . - حسب طريقة السداد :سندات تسدد عند تاريخ الاستحقاق ,سندات يمكن تسديد قيمتها قبل تاريخ استحقاقها . The syndicated loan is an external financing method that is borrowed by means of securities called bonds that include a loan issued by the borrower only a government, company or institution for a long term to finance the investments and major projects required to give the lender the right to meet his loan. His religion in the history of his entitlement. This type of financing is considered to be less expensive than equity financing as a way to allow the company or organization to maintain its independence in management, unlike financing by shares, which allows the entry of new partners who have the right to manage the company. Bond financing does not allow owners to interfere in the management of the company, but only to obtain benefits There are several types of bonds, including: - The issuer is divided into four types: international bonds, state bonds, government bonds, bonds issued by financial institutions and joint stock companies - By type of guarantee method: Bonds subject to certain banks, ordinary bonds with no guarantee. - According to the beneficiary's name: Bonds of the holder, nominal bonds - By their effects: convertible bonds, non-convertible bonds, bonds with a premium - According to the currency in which they are released: Bonds in the national currency of the issuer, securities issued in foreign currencies for the issuer. - By method of payment: Bonds payable on maturity, bonds that can be repaid before maturity.
قانون اعمال
Keywords: القرض السندي , أوراق مالية ,سندات , تمويل ,شركات ,مؤسسات مالية; Syndicated loans, securities, bonds, finance, companies, financial institutions